Sundanese Digital Gastronomy Literacy in Social Media - Pratiwi, Ilma; Valentina, Debi; Turgarini, Dewi (Politeknik Pariwisata NHI Bandung, 2021)
Social media able to attract digital netizen attention with various features. Social media can also be used as a way to attract user attention and to be able to dig deeper knowledge about Sundanese gastronomy. This study aims to analyze social media accounts containing Sundanese Gastronomy Literacy on Instagram and Youtube. This study wants to analyze and comparing what content is uploaded and how digital literation happen in the process in each social media platform. This study result social media used for promoting and educating about Sundanese Gastronomy. The more interesting the content uploaded, more engaging to follower will result in action whether it is buying, recommending, or coming to the site.